External Imbalances and Fiscal Policy in the Group of Three Countries : The Role of Stock-Flow Dynamics. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1989)
This paper discusses recent empirical research on the interplay between fiscal policies and external imbalances in the G3 countries, focusing on the stock-flow dynamics of public and foreign deficits and debt accumulation.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet